2019
DOI: 10.1192/bjo.2019.28
|View full text |Cite
|
Sign up to set email alerts
|

Crisis-planning interventions for people with psychotic illness or bipolar disorder: systematic review and meta-analyses

Abstract: Background Mental health services lack a strong evidence base on the most effective interventions to reduce compulsory admissions. However, some research suggests a positive impact of crisis-planning interventions in which patients are involved in planning for their future care during a mental health crisis. Aims This review aimed to synthesise randomised controlled trial (RCT) evidence on the effectiveness of crisis-planning interventions (for example advance statements and joint crisis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 24 publications
3
55
0
Order By: Relevance
“…The PACT is a model with explicit space and guidance for personalised input into medico-legal assessment, while also allowing ‘authentication’ of the document itself, through elements such as documented assessment of capacity when drafting and specification of review period. They are also designed to challenge the model of ADM as primarily a tool to avoid compulsory treatment ( de Jong et al, 2016 ; Molyneaux et al, 2019 ), by identifying and faciliating diverse outcomes; building, for example, on law reform supporting ‘self-binding’ in jurisdictions such as the Netherlands and Washington State ( Berghmans & van der Zanden, 2012 ; Varekamp, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PACT is a model with explicit space and guidance for personalised input into medico-legal assessment, while also allowing ‘authentication’ of the document itself, through elements such as documented assessment of capacity when drafting and specification of review period. They are also designed to challenge the model of ADM as primarily a tool to avoid compulsory treatment ( de Jong et al, 2016 ; Molyneaux et al, 2019 ), by identifying and faciliating diverse outcomes; building, for example, on law reform supporting ‘self-binding’ in jurisdictions such as the Netherlands and Washington State ( Berghmans & van der Zanden, 2012 ; Varekamp, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Advance decision making (ADM) for mental health crises is widely approved, but under-used and under-resourced, particularly when compared to ADM in physical healthcare settings. Existing research on ADM in severe mental illness (SMI) has confirmed interest amongst key stakeholders ( Hindley et al, 2019 ; Swanson, Swartz, Ferron, Elbogen, & van Dorn, 2006b ), together with some effectiveness in reducing coercion and increasing therapeutic alliance ( de Jong et al, 2016 ; Molyneaux et al, 2019 ; Thornicroft et al, 2013 ). However, difficulties in achieving uptake, engagement with legal provision and successful implementation are consistent ( Hindley et al, 2019 ; Morriss, Mudigonda, Bartlett, Chopra, & Jones, 2017 ; Swanson et al, 2006b ) and there is limited exploration of the diversity of potential outcomes beyond a reduction in compulsory admission.…”
Section: Introductionmentioning
confidence: 99%
“…1). [40][41][42][43][44][45][46][47][48][49] From these ten systematic reviews we retained and included in statistical re-analysis the three non-overlapping systematic reviews with the largest number of component studies ( Fig. 1 and supplementary material).…”
Section: Description Of Included Systematic Reviewsmentioning
confidence: 99%
“…De Jong et al (2016) includes two additional larger studies, which individually report no overall reduction in compulsory treatment, and conclude, somewhat confusingly, that there is a clinically significant reduction in compulsory admissions. A systematic review and meta-analysis commissioned by the IRMHA reported that crisis planning interventions, such as advance directives, reduced compulsory admissions but not voluntary or overall admissions (Molyneaux et al, 2018).…”
Section: Making the Case For Mental Health Adm: Empirical Evidencementioning
confidence: 99%